Sustainability : fundamentals and applications - Surampalli, Rao Y. (John Wiley & Sons, Inc., 2020)
"The book provides both fundamentals as well as key concepts of sustainability. The objective is to bring together a broad range of topics including basic concepts, impact assessment, environmental and socio-economic aspects of sustainability. In addition, the book also covers applications of sustainability in environmental, industrial, agricultural and food security, carbon cycle, infrastructural aspects. The motivation is to convince the reader about the essentiality of sustainability in ensuring the propitious future of earth systems. The book consists of two parts: Part 1 covers the fundamentals, whereas Part 2 mainly focuses on different applied aspects of sustainability"--